The role of phase difference components of ground motions in the torsional response of asymmetric buildings. - Alexander, Nicholas Andrew
It is demonstrated that the difference in phase content between orthogonal, horizontal, accelerograms can directly influence the effective (band-limited) torque energy applied to a plan asymmetric structure. This is not the case where a plan asymmetric structure is excited solely by a unidirectional, horizontal, accelerogram ground motion. It is shown that this effective torque energy is well correlated with building torsional (response) acceleration energy and element ductility demands for a broad class of multistorey structures. Nonlinear time-history analyses employing a database of accelerogram abstracted from USGS are used to quantify the influence of the phase difference content on these building responses. Bias in nonlinear time-history analyses based on a small sample of accelerograms caused by phase difference content is discussed.
Keywords: Phase difference component; Asymmetric building torsion